Functional Outcomes and Quality of Life after Restorative Proctocolectomy in Paediatric Patients: A Case-Control Study - Pellino, Gianluca (Hindawi Publishing Corporation, 2014)
Background. Restorative proctocolectomy with ileal-pouch anal anastomosis (IPAA) has some peculiarities in paediatric ulcerative colitis (UC). Aims. The primary aim was to compare the bowel function of patients undergoing IPAA between those operated on in childhood and adulthood. The secondary aim was to compare the quality of life (QoL) and outcomes for children between medical and surgical therapies. Method. Children undergoing IPAA were compared with adult patients undergoing IPAA between 2007 and 2012. Function was assessed 1 year after ileostomy closure. Function and QoL of medically managed paediatric patients were compared with their surgical counterparts. Results. Twelve paediatric IPAA patients were compared with 24 adult ones. Acute presentation was common in the former, usually after failed biological treatment. Recurrent pouchitis was more frequent in children. Younger patients exhibited a trend toward better discrimination and continence. QoL was excellent in both groups. Twelve medically treated children were enrolled for secondary aim. Functioning was similar in IPAA- and medically managed children, but the former had a better QoL, confirmed by parents' perception. Conclusions. Similar function is achieved by IPAA in childhood or adulthood. IPAA may offer a better QoL compared to prolonged medical management. The beneficial effects of IPAA experienced by children were similarly observed by their parents.